EVALUATION OF THE BLACK GARLIC FERMENTATION CHRACTERISTIC USING CAMION (BLACK GARLIC FERMENTATION MACHINE) - Melati Ayuning Putri; Maimunah Hindun Pulungan; Sukardi Sukardi (BPFP Faperta UNIB, 2020)
This study was to determine how the effect of fermentation time affected characteristics of black garlic using CAMION with a fermentation period of 10-20 days with an interval of 2 days and a temperature of 70 ± 1?C and a humidity of 70 ± 1%. The study used a Randomized Block Design (RCBD) with one factor, namely the fermentation time. There were 6 levels used in this study, namely 10 days, 12 days, 14 days, 16 days, 18 days, and 20 days with 3 repetitions. Dependent variables were water content, yield, physical color test, organoleptic, and e-nose. Data were analyzed using Microsoft Office Excel 2010, SPSS, if the significance value was significantly different, then the LSD test was performed at 5%. Organoleptic data were analyzed using the Friedman test, while electronic nose results were analyzed using the Minitab15 Statistical Software. Based on the results of the study, the fermentation time significantly affected the yield, water content, brightness color (L), reddish color (a *), yellowish color (b*). The fermentation time does not significantly affect the aroma of black onions, but it does have a significant effect on the color, texture, and taste of black onions. The scent that results from the analysis of the electronic nose showed that there was a difference in aroma between CAMION black onions and samples already on the market.